Nurses’ perceptions of continuous glucose monitoring in pediatric high-dependency care: a single-center survey of workflow and safety during management of an infant with hyperinsulinemic hypoglycemia - Soo Ting Joyce Lim; Yuen Ching Angela Hui; Nazimah Binte Mohamed Sani; Daniel Chan (International Diabetes Nursing, 2026)
Background: Dysglycemia is associated with increased morbidity and mortality in critically ill pediatric patients. Continuous glucose monitoring (CGM) offers real-time glucose trend data, addressing limitations of point-of-care (POC) testing, such as intermittent readings and high workload. However, successful implementation of CGM in high-dependency (HD) pediatric care depends significantly on nurses’ perceptions and acceptance, which could better manage nursing workload. Objective: This study explores nurses’ perceptions of CGM in a pediatric HD setting, focusing on factors that influence CGM adoption for workload management, using a case formulation framework, including predisposing, perpetuating, precipitating, and protective factors. Methods: A single-center study was conducted at KK Women’s and Children’s Hospital, involving 45 HD nurses who took part in a validated 20-item survey. Training on CGM implementation and guidelines was provided, and descriptive statistics were used to analyze survey responses. A specific case of an infant with hyperinsulinemic hypoglycemia (HH) was included to illustrate CGM’s clinical application. The study was conducted in accordance with institutional guidelines, ensuring confidentiality of patient and nurse data. Results: Most nurses (86%) reported that CGM was easy to use and reduced their workload compared to POC testing. In addition, 88% of nurses agreed that CGM, when combined with POC testing, enhanced patient safety. Despite limited familiarity with CGM prior to implementation (37% reported no prior experience), 86% of nurses felt comfortable using CGM after training, which was primarily delivered through peer-led handovers. Barriers to adoption included challenges with calibration protocols and perceived accuracy (54% reported CGM readings as accurate). Overall, 82% of nurses recommended CGM for continued use in HD care. Conclusion: The CGM is perceived positively by nurses for its ability to enhance patient safety, improve workflow efficiency, and reduce workload in pediatric HD settings. However, successful implementation requires structured training, clear guidelines, and ongoing support to address barriers such as limited familiarity and calibration challenges. Future research should evaluate CGM’s cost-effectiveness, clinical outcomes, and long-term impact on glycemic control in acute inpatient pediatric care.